Surface modified medical titanium material with antibacterial effect as well as preparation method and application of surface modified medical titanium material

By loading gold nanoparticles and fixing PHMB on the surface of medical titanium materials, the problem of insufficient antibacterial performance of titanium materials is solved, and effective inhibition of bacteria and safety of cells is achieved.

CN119701093AActive Publication Date: 2025-03-28JIAMUSI UNIVERSITY
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202510018997.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-07
Publication Date
2025-03-28
Estimated Expiration
2045-01-07

AI Technical Summary

Technical Problem

Existing medical titanium metal materials lack antibacterial properties, which can easily lead to bacterial infection and implant failure.

Method used

Polyhexamethylene biguanide hydrochloride (PHMB) is immobilized on the surface of the gold nanoparticles to form a modified material with antibacterial effects.

Benefits of technology

It achieves significant antibacterial effects on E. coli and Staphylococcus aureus, while reducing the toxic side effects of PHMB on cells, ensuring that the modified titanium material is harmless to cells.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119701093A_ABST
    Figure CN119701093A_ABST
Patent Text Reader

Abstract

The invention provides a surface modified medical titanium material with an antibacterial effect and a preparation method and application thereof, and belongs to the technical field of metal material surface modification. According to the surface-modified medical titanium material, antibacterial modification treatment is carried out on the surface of pure titanium, specifically, gold nanoparticles are adopted as carriers to load polyhexamethylene biguanide hydrochloride, and the modified titanium material with antibacterial property and extremely low cytotoxicity is obtained; the preparation method of the surface modified medical titanium material comprises the steps that piranha washing liquor is adopted for treatment, numerous hydroxyl functional groups are obtained on the titanium surface, then 3-aminopropyltrimethoxysilane is adopted for grafting and loading, and then gold nanoparticles and polyhexamethylene biguanide hydrochloride are adopted for preparing the surface modified medical titanium material. A titanium modified material loaded with gold nanoparticle-polyhexamethylene biguanide hydrochloride is obtained through the electrostatic adsorption effect; the pure titanium modified material prepared by the invention has a remarkable antibacterial effect, has no toxic effect on cells, and can effectively prevent and treat postoperative infection of the titanium implant.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of surface modification of metal materials, and in particular relates to a surface-modified medical titanium material with antibacterial effect, a preparation method and application thereof. Background Art

[0002] With the trend of population aging and the intensification of social activities, the number of fractures and bone defects caused by traffic, sports, industry, etc. has increased, and people's demand for bone tissue replacement and repair materials has increased year by year. Biomedical titanium metal has the advantages of low density, low elastic modulus, good corrosion resistance and fatigue resistance, and good biocompatibility. It has become the preferred material for hard tissue implants. However, titanium metal does not have antibacterial properties and is prone to bacterial infection. Bacteria adhere to the surface of titanium implants and secrete polysaccharide matrix, fibrin, lipoprotein and other polysaccharide complexes to form biofilms. The formation of biofilms not only absorbs nutrients from the surrounding environment, escapes the attack of the human body's defense system, but also has strong resistance to most antibiotics. Therefore, once bacterial infection occurs, treatment is very difficult and easily leads to the failure of titanium implants. The surface of titanium implants is in direct contact with the human body environment, and the behavior of bacteria is regulated by the characteristics of the titanium surface. Therefore, constructing an antibacterial film on the titanium surface to avoid bacterial adhesion and proliferation on the surface of titanium implants has become one of the hot spots in the research of titanium implant materials.

[0003] Gold nanoparticles (GNPs) are widely used in biomedical fields such as photothermal therapy, controlled drug release, and bioimaging due to their low toxicity, plasmon resonance absorption characteristics, and easy surface functionalization. Therefore, loading gold nanoparticles on the surface of medical pure titanium can effectively improve the bone integration ability of titanium materials, such as the wet chemical method of loading gold nanoparticles on titanium oxide nanotubes disclosed in Chinese Patent 103451705A. The substrate modified with gold nanoparticles has good biocompatibility and can promote the adhesion of proteins and the proliferation and osteogenic differentiation of bone marrow mesenchymal stem cells. The surface of gold nanoparticles is negatively charged, so polyhexamethylene biguanide hydrochloride (PHMB) can be stably fixed on the surface of titanium materials through electrostatic adsorption. Therefore, gold nanoparticles can act as a bridge connecting titanium and PHMB, so that the prepared gold nanoparticles and PHMB-modified titanium surfaces have obvious antibacterial effects. This titanium surface modification preparation process has the advantages of easy operation, stable process, low cost, and easy promotion and application.

[0004] PHMB is an antibacterial agent that is positively charged. After adsorbing with negatively charged bacteria, it can block the respiratory tract of bacteria and inhibit bacterial division. The biguanide group in polyhexamethylene biguanide hydrochloride can also bind to the phosphatidylglycerol bilayer on the surface of bacteria, causing damage to the bacterial cell wall, reduced membrane fluidity, leakage of ions, adenosine triphosphate and proteins, and ultimately leading to bacterial death. However, free PHMB is concentration-dependent in clinical antibacterial treatment. High doses of PHMB can cause the collapse of normal cell membrane structure, form transmembrane pores, rupture cell membranes, leak intracellular substances, and bring certain toxic side effects to the human body. Therefore, how to reduce the action concentration of PHMB while using the antibacterial properties of PHMB has not been reported yet. Summary of the invention

[0005] In view of the deficiencies in the prior art, the present invention discloses a surface-modified medical titanium material with antibacterial effect, a preparation method and application thereof, so as to solve the problem of poor antibacterial performance of existing medical titanium metal materials. The surface of pure titanium is subjected to antibacterial surface modification treatment, specifically, polyhexamethylene biguanide hydrochloride is loaded with gold nanoparticles as a carrier, so as to obtain a modified titanium material with both antibacterial property and low cytotoxicity.

[0006] A surface-modified medical titanium material with antibacterial effect is a modified material in which gold nanoparticles and polyhexamethylene biguanide hydrochloride are loaded on the surface of pure titanium, obtained by sequentially immersing pure titanium in a gold nanoparticle suspension and a polyhexamethylene biguanide hydrochloride solution; The method for preparing the surface-modified medical titanium material having antibacterial effect comprises the following steps: Step S1: Pure titanium surface pretreatment The pure titanium is ultrasonically cleaned in a cleaning solution for at least two times, then ultrasonically cleaned with deionized water, dried, immersed in a piranha cleaning solution, then ultrasonically cleaned with deionized water, and dried to obtain a pure titanium sample; Step S2: Preparation of gold nanoparticles The chloroauric acid solution is heated to boiling, and then the sodium citrate solution is added, and the heating and boiling are continued for 10-30 minutes to obtain a gold nanoparticle suspension; Step S3: Loading of gold nanoparticles The pure titanium sample obtained in step S1 is ultrasonicated in an aqueous solution of 3-aminopropyltrimethoxysilane (APS), and then the pure titanium sample is immersed in a suspension of gold nanoparticles with negatively charged citrate ions on the surface obtained in step S2, and allowed to stand to obtain a titanium sample loaded with gold nanoparticles; Step S4: Loading of polyhexamethylene biguanide hydrochloride (PHMB) The titanium sample loaded with gold nanoparticles was immersed in a polyhexamethylene biguanide hydrochloride (PHMB) solution and allowed to stand, then washed and dried to obtain a surface-modified medical titanium material.

[0007] The cleaning solution in step S1 includes hydrofluoric acid, concentrated nitric acid and deionized water, and the volume ratio of hydrofluoric acid, concentrated nitric acid and deionized water is (1-3): (4-6): 34; The piranha washing solution in step S1 is composed of concentrated sulfuric acid and hydrogen peroxide, and the volume ratio of concentrated sulfuric acid to hydrogen peroxide is (2.5-3.5):1; the soaking time in the piranha washing solution is 2-5 hours; The ultrasonic cleaning time in step S1 is 5-10 minutes; The volume ratio of the chloroauric acid solution to the sodium citrate solution in step S2 is 100:3-8; The mass concentration of the chloroauric acid solution in step S2 is 0.5-2%, and the mass concentration of the sodium citrate solution is 1-3%; The volume fraction of 3-aminopropyltrimethoxysilane in the 3-aminopropyltrimethoxysilane aqueous solution in step S3 is 3-8%; The ultrasonic time in step S3 is 1-3h; The standing time in step S3 is 12-48 hours; The mass volume concentration of the polyhexamethylene biguanide hydrochloride (PHMB) solution in step S4 is 15-30 mg / ml; The standing time in step S4 is 12-24 hours.

[0008] The above-mentioned surface-modified medical titanium material with antibacterial effect is used as a titanium implant in the biomedical field.

[0009] The beneficial effects of the present invention are: 1. The use of piranha lotion in the present invention will produce numerous -OH functional groups on the titanium surface, which is beneficial to the subsequent grafting and loading of 3-aminopropyltrimethoxysilane (APS). The aqueous solution of 3-aminopropyltrimethoxysilane (APS) can form a silanol structure by step-by-step hydrolysis in an aqueous environment. The siloxane oligomer formed by dehydration condensation of silanol can further react with -OH on the titanium surface treated with piranha lotion to form a Si-O covalent bond through dehydration condensation reaction, so that APS is grafted on the titanium surface. Since APS contains a positively charged -NH2 group, the titanium surface grafted with APS exhibits a higher positive charge in a liquid environment; the surface of the gold nanoparticles is negatively charged while PHMB is positively charged, and the gold nanoparticles and polyhexamethylene biguanide hydrochloride are sequentially loaded by electrostatic adsorption, and finally a titanium modified material loaded with gold nanoparticles-polyhexamethylene biguanide hydrochloride is obtained; 2. The pure titanium modified material loaded with gold nanoparticles and polyhexamethylene biguanide hydrochloride prepared by the present invention has a relatively obvious antibacterial effect on Escherichia coli and Staphylococcus aureus, and can effectively prevent and treat postoperative infection of titanium implants; the pure titanium modified material loaded with gold nanoparticles and polyhexamethylene biguanide hydrochloride has good biocompatibility of gold nanoparticles, and the trace loading amount of polyhexamethylene biguanide hydrochloride reduces the toxic side effects of high-concentration polyhexamethylene biguanide hydrochloride on cells, so that the modified titanium surface has no obvious toxic effect on cells; 3. The polyhexamethylene biguanide hydrochloride used in the present invention is a cationic antibacterial agent, which is fixed on the surface of biomedical pure titanium material by electrostatic self-assembly technology. The method is simple and efficient, the preparation process is stable and controllable, the operation is simple, the cost is low, and it is easy to promote and apply. BRIEF DESCRIPTION OF THE DRAWINGS

[0010] Figure 1 The scanning electron microscope morphology image of the pure titanium surface after the modification treatment of the present invention, in which: Ti represents the scanning electron microscope morphology image of the titanium surface after being treated with piranha lotion, Ti-GNP represents the scanning electron microscope morphology image of the titanium surface loaded with gold nanoparticles, and Ti-GNP-PHMB represents the scanning electron microscope morphology image of the titanium surface loaded with gold nanoparticles and polyhexamethylene biguanide hydrochloride; Figure 2 EDS images of titanium surfaces loaded with gold nanoparticles and polyhexamethylene biguanide hydrochloride; Figure 3 The figure is a graph showing the variation of the Zeta potential of the pure titanium surface after the modification treatment according to the present invention with the pH value of the electrolyte, in which: Ti represents the variation curve of the Zeta potential of the titanium surface after being treated with piranha lotion with the pH value of the electrolyte, Ti-APS represents the variation curve of the Zeta potential of the titanium surface after being treated with piranha lotion and 3-aminopropyltrimethoxysilane with the pH value of the electrolyte, Ti-GNP represents the variation curve of the Zeta potential of the titanium surface loaded with gold nanoparticles with the pH value of the electrolyte, and Ti-GNP-PHMB represents the variation curve of the Zeta potential of the titanium surface loaded with gold nanoparticles and polyhexamethylene biguanide hydrochloride with the pH value of the electrolyte; Figure 4 The effect of the pure titanium surface modified by the present invention on the activity of Escherichia coli, in which: Ti represents the activity of Escherichia coli on the titanium surface treated with piranha lotion, Ti-GNP represents the activity of Escherichia coli on the titanium surface loaded with gold nanoparticles, and Ti-GNP-PHMB represents the activity of Escherichia coli on the titanium surface loaded with gold nanoparticles and polyhexamethylene biguanide hydrochloride; Figure 5The effect of the pure titanium surface modified by the present invention on the activity of Staphylococcus aureus, in which: Ti represents the activity of Staphylococcus aureus on the titanium surface treated with piranha lotion, Ti-GNP represents the activity of Staphylococcus aureus on the titanium surface loaded with gold nanoparticles, and Ti-GNP-PHMB represents the activity of Staphylococcus aureus on the titanium surface loaded with gold nanoparticles and polyhexamethylene biguanide hydrochloride; Figure 6 : is a scanning electron microscope image of Escherichia coli on a pure titanium surface after modification by the present invention, wherein: Ti represents a scanning electron microscope image of Escherichia coli on a titanium surface treated with piranha lotion, Ti-GNP represents a scanning electron microscope image of Escherichia coli on a titanium surface loaded with gold nanoparticles, and Ti-GNP-PHMB represents a scanning electron microscope image of Escherichia coli on a titanium surface loaded with gold nanoparticles and polyhexamethylene biguanide hydrochloride; Figure 7 : is a scanning electron microscope image of Staphylococcus aureus on a pure titanium surface after modification by the present invention, in which: Ti represents a scanning electron microscope image of Staphylococcus aureus on a titanium surface treated with piranha lotion, Ti-GNP represents a scanning electron microscope image of Staphylococcus aureus on a titanium surface loaded with gold nanoparticles, and Ti-GNP-PHMB represents a scanning electron microscope image of Staphylococcus aureus on a titanium surface loaded with gold nanoparticles and polyhexamethylene biguanide hydrochloride; Figure 8 The present invention is a scanning electron microscope image of human osteosarcoma cells after being cultured on the pure titanium surface modified by the present invention for 24 hours. In the figure: Ti represents the scanning electron microscope morphology image of human osteosarcoma cells on the titanium surface treated with piranha lotion after being cultured for 24 hours, Ti-GNP represents the scanning electron microscope morphology image of human osteosarcoma cells on the titanium surface loaded with gold nanoparticles after being cultured for 24 hours, and Ti-GNP-PHMB represents the scanning electron microscope morphology image of human osteosarcoma cells on the titanium surface loaded with gold nanoparticles and polyhexamethylene biguanide hydrochloride after being cultured for 24 hours. DETAILED DESCRIPTION

[0011] The present invention is further described below in conjunction with the accompanying drawings and the following embodiments. It should be understood that the following embodiments are only used to illustrate the present invention rather than to limit the present invention.

[0012] The amount of pure titanium used in the technical solution of the present invention is not specifically limited. In the process of surface modification of pure titanium, the amount of cleaning solution, piranha cleaning solution, 3-aminopropyltrimethoxysilane and polyhexamethylene biguanide hydrochloride (PHMB) used for immersion is sufficient to ensure that the pure titanium sample can be completely immersed; In the embodiment of the present invention, the size of pure titanium is 10 mm×10 mm×1 mm, and the amount of cleaning solution, piranha cleaning solution, 3-aminopropyltrimethoxysilane and polyhexamethylene biguanide hydrochloride (PHMB) used is 1-3 ml; The mass concentration of hydrofluoric acid in the cleaning solution of the present invention is 44-51%, and the mass concentration of concentrated nitric acid is 65-68%; the piranha cleaning solution is composed of concentrated sulfuric acid with a mass concentration of 95-98% and hydrogen peroxide with a mass concentration of 30%; The invention requires that the surface of the pure titanium be polished before being immersed in a cleaning solution, and then immersed in acetone, ethanol and deionized water in sequence and ultrasonically cleaned for 5-10 minutes each, so as to remove stains on the titanium surface.

[0013] Example 1 Pure titanium surface pretreatment After polishing, pure titanium of 10mm×10mm×1mm was ultrasonically cleaned with acetone, ethanol and deionized water in turn, each for 5 minutes, and then dried for use; it was ultrasonically cleaned twice with a mixed acid cleaning solution with a volume ratio of HF:HNO3:H2O=1:5:34, each for 5 minutes, and then ultrasonically cleaned with deionized water for 5 minutes, and then dried for use; the pure titanium sample after the above acid treatment was immersed in a piranha cleaning solution of concentrated sulfuric acid and hydrogen peroxide with a volume ratio of 2.5:1 for 2 hours, and then ultrasonically cleaned with deionized water for 5 minutes. After drying, the titanium material (Ti) treated with the piranha cleaning solution was properly preserved.

[0014] Example 2 Pure titanium surface pretreatment After polishing, pure titanium of 10mm×10mm×1mm was ultrasonically cleaned with acetone, ethanol and deionized water in turn, each for 5 minutes, and then dried for use; it was ultrasonically cleaned twice with a mixed acid cleaning solution with a volume ratio of HF:HNO3:H2O=3:6:34, each for 5 minutes, and then ultrasonically cleaned with deionized water for 5 minutes, and then dried for use; the pure titanium sample after the above acid treatment was immersed in a piranha cleaning solution of concentrated sulfuric acid and hydrogen peroxide with a volume ratio of 3.5:1 for 5 hours, and then ultrasonically cleaned with deionized water for 5 minutes. After drying, the titanium material (Ti) treated with piranha cleaning solution was properly preserved.

[0015] Figure 1 (Ti) is the surface morphology of the medical titanium material obtained by the modification treatment in Example 1, and the figure shows that a honeycomb multi-level pore nanostructure appears on the surface of the modified material; Figure 3(Ti) is the curve of the Zeta potential of the medical titanium material surface modified in Example 1 versus the pH of the electrolyte. It can be seen that the Zeta potential of the medical titanium material surface modified in Example 1 gradually decreases with increasing pH value. Since the pH value of the in vivo environment is around 7.4, the Zeta potential of the material at a pH value of 7.4 is of particular concern. It can be seen that the Zeta potential of the Ti surface at a pH value of 7.4 is -54 mV, indicating that the surface of the medical titanium material modified in Example 1 forms a surface containing a large number of -OH groups, which is beneficial to the subsequent grafting of APS and electrostatic adsorption of gold nanoparticles.

[0016] Example 3 Gold nanoparticle loading 100 ml of 0.5% chloroauric acid solution was heated to boiling, and then 5 ml of 1% sodium citrate solution was added, and the heating was continued for 10 min to obtain a gold nanoparticle suspension; The titanium material treated in Example 1 was ultrasonically immersed in 2 ml of a 3% by volume 3-aminopropyltrimethoxysilane solution for 1 h, ultrasonically cleaned with deionized water for 5 min, and dried to obtain a titanium material treated with a silane coupling agent (Ti-APS). The titanium material was then immersed in 2 ml of the gold nanoparticle suspension prepared above and allowed to stand for 12 h, ultrasonically cleaned with deionized water for 5 min, and dried to obtain a titanium material loaded with gold nanoparticles (Ti-GNP).

[0017] Example 4 Gold nanoparticle loading 100 ml of 2% chloroauric acid solution was heated to boiling, and then 8 ml of 3% sodium citrate solution was added, and the heating was continued for 30 minutes to obtain a gold nanoparticle suspension; The titanium material treated in Example 1 was ultrasonically immersed in 3 ml of 8% by volume 3-aminopropyltrimethoxysilane solution for 3 h, ultrasonically cleaned with deionized water for 5 min, and dried to obtain a titanium material treated with a silane coupling agent (Ti-APS). The titanium material was then immersed in 2 ml of the gold nanoparticle suspension prepared above and allowed to stand for 48 h, ultrasonically cleaned with deionized water for 5 min, and dried to obtain a titanium material loaded with gold nanoparticles (Ti-GNP).

[0018] Figure 3(Ti-APS) is the curve of the Zeta potential of the medical titanium material surface obtained by 3-aminopropyltrimethoxysilane treatment in Example 3 as a function of the pH value of the electrolyte. It can be seen that the Zeta potential of the medical titanium material surface obtained by the modification treatment in Example 3 gradually decreases as the pH value increases. By comparing the surface potentials of Ti and Ti-APS, it is found that the surface potential of Ti-APS is higher than that of Ti at the same pH value, indicating that the Zeta potential of the Ti-APS surface modified with APS is significantly increased due to the positively charged -NH2 group in the coupling agent. The gold nanoparticles prepared by the sodium citrate method are coated with negatively charged citrate ions, so the gold nanoparticles can be loaded on the Ti-APS surface by electrostatic attraction. Figure 3 (Ti-GNP) is the curve of the surface Zeta potential of the medical titanium material obtained by the modification treatment in Example 3 versus the pH of the electrolyte. By comparing the surface potentials of Ti-APS and Ti-GNP, it is found that the surface potential of Ti-GNP is lower than that of Ti-APS at the same pH value, indicating that the surface Zeta potential value of the Ti-GNP surface is reduced due to the negatively charged gold nanoparticles loaded on it; Figure 1 (Ti-GNP) is the surface morphology of the medical titanium material obtained by the modification treatment in Example 3. The figure shows that the gold nanoparticles are uniformly loaded on the surface of Ti-GNP.

[0019] Example 5 The gold nanoparticle-loaded titanium material treated in Example 3 was immersed in 3 ml of a polyhexamethylene biguanide hydrochloride solution having a mass volume concentration of 15 mg / ml and allowed to stand for 12 h. After washing and drying, a surface-modified medical titanium material loaded with gold nanoparticles-polyhexamethylene biguanide hydrochloride (Ti-GNP-PHMB) was obtained.

[0020] Example 6 The gold nanoparticle-loaded titanium material treated in Example 3 was immersed in 1 ml of a polyhexamethylene biguanide hydrochloride solution having a mass volume concentration of 30 mg / ml and allowed to stand for 24 h. After washing and drying, a surface-modified medical titanium material loaded with gold nanoparticles-polyhexamethylene biguanide hydrochloride (Ti-GNP-PHMB) was obtained.

[0021] Figure 1 (Ti-GNP-PHMB) is the surface morphology of the medical titanium material obtained by the modification treatment in Example 5. The figure shows that the titanium surface loaded with polyhexamethylene biguanide hydrochloride retains a structure similar to that of Ti-GNP, indicating that loading with polyhexamethylene biguanide hydrochloride will not affect the surface morphology of the material treated in Example 3; Figure 2This is the energy spectrum curve of the medical titanium material obtained by the modification treatment in Example 5. It can be seen from the figure that the surface components of the material contain Ti, O, Si, Au, and Cl elements, among which the Si element comes from the silane coupling agent, the Au element comes from the gold nanoparticles, and the Cl element comes from polyhexamethylene biguanide hydrochloride; Figure 3 (Ti-GNP-PHMB) is the curve of the change of the surface Zeta potential of the titanium material obtained by the modification treatment in Example 5 with the pH of the electrolyte. By comparing the surface potentials of Ti-GNP and Ti-GNP-PHMB, it is found that the surface potential of Ti-GNP-PHMB is higher than that of Ti-GNP at the same pH value, indicating that the surface Zeta potential value of the Ti-GNP-PHMB surface is increased due to the loading of positively charged polyhexamethylene biguanide hydrochloride.

[0022] The antibacterial activity of the titanium materials modified by the above-mentioned Examples 1, 3 and 5 was evaluated by using Gram-negative bacteria Escherichia coli and Gram-positive bacteria Staphylococcus aureus. The specific method is as follows: The sample to be tested was sterilized in 75% ethanol for 2 hours, and 60 μL of 10 7 cfu / ml of bacterial solution was dropped on the sterilized sample surface and cultured in a 37°C constant temperature incubator for 24 hours. Then, AlamarBlue solution was added and cultured in a 37°C constant temperature incubator for another 4 hours. The absorbance was tested at 570nm and 600nm using an ELISA reader, and the bacterial activity was calculated according to the reagent instructions. The results are as follows: Figure 4 and Figure 5 As shown in the figure, the activity of Escherichia coli and Staphylococcus aureus on the surfaces of Ti-GNP and Ti-GNP-PHMB is lower than that of the Ti sample, while the activity of Escherichia coli and Staphylococcus aureus on Ti-GNP-PHMB is greatly reduced, indicating that the antibacterial effect of Ti-GNP material is weak, while Ti-GNP-PHMB material has higher antibacterial efficiency against Escherichia coli and Staphylococcus aureus.

[0023] The antibacterial activity of the titanium materials modified by the above-mentioned Examples 1, 3 and 5 was further evaluated by observing the morphology of Escherichia coli and Staphylococcus aureus using a scanning electron microscope (SEM). The specific method was as follows: the sample to be tested was sterilized in 75% ethanol for 2 h, 60 μL of 10 7 cfu / ml of bacterial solution was dropped on the sterilized sample surface and cultured in a 37°C constant temperature incubator for 24 hours. Then, 2.5% glutaraldehyde solution was added to fix the bacteria. Gradient concentrations of ethanol and hexamethyldisilane were used for dehydration and drying. Finally, the morphology of bacteria on the sample surface was observed under SEM. Figure 6 and Figure 7The scanning electron microscope morphology images of Escherichia coli and Staphylococcus aureus on the surface of the titanium materials modified in Examples 1, 3 and 5 for 24 hours show that the bacteria on the Ti sample have a complete surface and obvious filamentous pseudopodia, indicating that the bacteria have good activity. Pits and wrinkles appeared on the surface of several bacteria on the Ti-GNP sample, indicating that the growth of Escherichia coli and Staphylococcus aureus on the Ti-GNP sample was inhibited to a certain extent, while the bacteria on the Ti-GNP-PHMB sample showed bacterial lysis and cytoplasmic outflow, indicating that the titanium material modified in Example 5 above has good antibacterial ability.

[0024] The activity test of modified titanium materials inoculated with human osteosarcoma cells (MG63) was used to simulate the application of modified medical titanium materials as titanium implants in biomedicine: The cytotoxicity of the titanium materials modified by the above-mentioned Examples 1, 3 and 5 was evaluated by an activity test of human osteosarcoma cells (MG63) cultured in vitro for 24 hours. The specific method was as follows: after the sample was sterilized, 2×10 4 1 ml of cell suspension with a concentration of 100 cells / ml was inoculated on the sample surface and cultured in a constant temperature incubator at 37°C for 24 h. Then, 2.5% glutaraldehyde solution was added to fix the cells. Gradient concentrations of ethanol and hexamethyldisilane were used to dehydrate and dry the cells. Finally, the morphology of MG63 on the sample surface was observed under SEM. The results are as follows: Figure 8 As shown; Materials with antibacterial properties generally have a certain degree of toxicity to cells. Figure 8 It can be seen that the results of the cell experiment show that the Ti-GNP-PHMB sample has an antibacterial effect on Escherichia coli and Staphylococcus aureus, while having no obvious cytotoxicity to cells, that is, the Ti-GNP-PHMB sample has an inhibitory effect on bacteria, but has no obvious toxicity to human cells; Figure 8 The cell images show that the cell appearances of the three samples are similar. There is no obvious change in the morphology of MG63 cells on Ti, Ti-GNP, and Ti-GNP-PHMB, indicating that the cell activity of the titanium sample in Example 5 after GNP and PHMB is not significantly decreased compared with the sample before modification.

[0025] The above embodiments are only partial implementation schemes of the present invention, but the protection scope of the present invention is not limited thereto. The various aspects and implementation schemes of the present invention disclosed herein are only examples of specific ways to make and use the present invention. The present invention is not limited to any limitation due to the sequence and specific operations of the embodiments. Any replacement and changes that can be easily thought of by any researcher familiar with the technical field within the technical scope disclosed by the present invention should be included in the protection scope of the present invention.

Claims

1. A surface-modified medical titanium material with antibacterial effect, characterized in that: The surface-modified medical titanium material with antibacterial effect is a modified material in which gold nanoparticles and polyhexamethylene biguanide hydrochloride are loaded on the surface of pure titanium, obtained by sequentially immersing pure titanium in a gold nanoparticle suspension and a polyhexamethylene biguanide hydrochloride solution; The components and volume fractions contained in the gold nanoparticle suspension are: chloroauric acid solution: sodium citrate solution = 100: 3-8; The mass volume concentration of the polyhexamethylene biguanide hydrochloride solution is 15-30 mg / ml.

2. A method for preparing the surface-modified medical titanium material with antibacterial effect according to claim 1, characterized in that: The following steps are involved: Step S1: Loading of gold nanoparticles The pretreated pure titanium sample is ultrasonicated in a 3-aminopropyltrimethoxysilane aqueous solution, and then the pure titanium sample is immersed in a gold nanoparticle suspension and allowed to stand to obtain a titanium sample loaded with gold nanoparticles; Step S2: Loading of polyhexamethylene biguanide hydrochloride The titanium sample loaded with gold nanoparticles is immersed in a polyhexamethylene biguanide hydrochloride solution and allowed to stand, and then washed and dried to obtain a surface-modified medical titanium material with antibacterial effect.

3. The method for preparing the surface-modified medical titanium material with antibacterial effect according to claim 2, characterized in that: The processing process of the pretreated pure titanium sample in step S1 includes: ultrasonically cleaning the pure titanium in a cleaning solution for at least two times, then ultrasonically cleaning it with deionized water, drying it and immersing it in a piranha cleaning solution, then ultrasonically cleaning it with deionized water, and drying it to obtain the pretreated pure titanium sample; the ultrasonic cleaning time is 5-10 minutes.

4. The method for preparing the surface-modified medical titanium material with antibacterial effect according to claim 3, characterized in that: The cleaning solution includes hydrofluoric acid, concentrated nitric acid and deionized water, and the volume ratio of hydrofluoric acid, concentrated nitric acid and deionized water is (1-3): (4-6): 34; the piranha cleaning solution is composed of concentrated sulfuric acid and hydrogen peroxide, and the volume ratio of concentrated sulfuric acid and hydrogen peroxide is (2.5-3.5): 1; the immersion time in the piranha cleaning solution is 2-5 hours.

5. The method for preparing the surface-modified medical titanium material with antibacterial effect according to claim 2, characterized in that: The volume fraction of 3-aminopropyltrimethoxysilane in the 3-aminopropyltrimethoxysilane aqueous solution in step S1 is 3-8%.

6. The method for preparing the surface-modified medical titanium material with antibacterial effect according to claim 2, characterized in that: The preparation process of the gold nanoparticle suspension in step S1 is: heating the chloroauric acid solution to boiling, adding the sodium citrate solution, and continuing to heat and boil for 10-30 minutes to obtain the gold nanoparticle suspension.

7. The method for preparing the surface-modified medical titanium material with antibacterial effect according to claim 6, characterized in that: The mass concentration of the chloroauric acid solution is 0.5-2%; the mass concentration of the sodium citrate solution is 1-3%.

8. The method for preparing the surface-modified medical titanium material with antibacterial effect according to claim 2, characterized in that: The ultrasonication time in step S1 is 1-3 hours, and the standing time is 12-48 hours.

9. The method for preparing the surface-modified medical titanium material with antibacterial effect according to claim 2, characterized in that: The standing time in step S2 is 12-24 hours.

10. Use of the surface-modified medical titanium material with antibacterial effect as claimed in any one of claims 1 to 9 as a titanium implant in the biomedical field.

Citation Information

Patent Citations

  • Preparation method of gold-loaded nanotube thin film on surface of medical titanium

    CN103451705A

  • Surface-modified medical titanium metal material and preparation method thereof

    CN103540934A

  • Method for constructing slow release system for medicament on surface of medical titanium alloy implant

    CN105664259A

  • Preparation method of medical titanium metal surface rapid antibacterial coating

    CN116850341A